ROLE OF IMMUNOHISTOCHEMISTRY IN SUBTYPING RENAL CELL CARCINOMAS WITH OVERLAPPING MORPHOLOGICAL FEATURES - Tariq, Naima; Mamoon, Nadira; Haroon, Asna; Ali, Zafar; Ahmad, Imran Nazir (Journal of Ayub Medical College Abbottabad, 2018)
Background: Renal cell carcinoma (RCC), accounts for 2-3% of all new cancers diagnosed. Most renal tumours have characteristic histological features, which help in their sub classification. However, some cases do show overlapping morphology which pose a diagnostic challenge for the pathologists. Tumour ancillary studies such as immunohistochemistry (IHC) may play a significant role in segregation of these tumours. This study was undertaken to determine the role of IHC in diagnosing these tumours. Methods: It was a Cross-sectional, prospective study over a period of two years from 1st January 2014 to 30th December 2015. It was carried out in histopathology laboratory of Shifa International Hospital, Islamabad. A total of fifty-five (n=55) nephrectomy specimens having RCC subtypes were included. A specific morphological diagnosis was rendered in each case on H&E.. A panel of six immunohistochemical markers CK7, CD10, CD117, CA IX, AMACR and Vimentin was then applied in each case and a final diagnosis considering both morphology and IHC was given. Statistical analysis was done using SPSS version 20.0. Mean and SD were calculated for quantitative variables where as frequencies and percentages were calculated for qualitative variables.Results: Out of a total of 55 cases, 36 (65.55%) were males whereas 19(34.5%) were females. The mean age of patients was 54.04±14.40 years. Clear cell RCC comprised 70.9% (n=39), Papillary RCC 14.5% (n=8), Chromophobe RCC 10.9% (n=6) and clear cell papillary RCC 3.6% (n=2) of cases on morphology. After application of IHC stains in all cases, 83.6%(n=46) of cases were found to have correct diagnosis on H& E. However, 16.4% (n=9) of cases could not be correctly diagnosed on morphology alone and it was in these cases that IHC played a major role in reaching a final diagnosis. Conclusion Although most RCC subtypes display a characteristic morphology on H&E, in a significant proportion of the cases there are considerable overlapping morphological features. Our study shows that a correct diagnosis, cannot be made on H & E alone in a notable number of cases. Therefore, IHC should be applied in all cases to reach a final diagnosis, which has both prognostic and therapeutic implications. Keywords: RCC subtypes; Immunohistochemistry; Clear cell papillary RCC